2016
DOI: 10.1016/j.ijsu.2016.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Combined intravenous and topical tranexamic acid versus intravenous use alone in primary total knee and hip arthroplasty: A meta-analysis of randomized controlled trials

Abstract: Based on our study, Combined use of intravenous and topical TXA is more effective than intravenous TXA alone in primary total knee or hip arthroplasty without increasing the risk of thromboembolic complications. Further high quality studies with more patients are needed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Considering the safety impact of pharmacist interventions, we found no significant increase in adverse events, which was in accord with the findings of other studies . During the intervention phase, adverse events included surgical site infections, haematoma and DVT.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the safety impact of pharmacist interventions, we found no significant increase in adverse events, which was in accord with the findings of other studies . During the intervention phase, adverse events included surgical site infections, haematoma and DVT.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have shown that the application of a tourniquet decreases intraoperative blood loss in TKA, [10,11] and the topical application of tranexamic acid reduces the drainage volume after TKA. [1214] However, dominant blood loss should not be underestimated when volumes can range from 380 to 800 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, two RCTs concluded that intra-articular regimen of TXA is as effective as three doses IV regimen in preventing blood loss without any difference in thromboembolic complications[93,94]. In addition to all these studies some authors have noticed that the combination of IV and intra-articular TXA is more effective than either regimen used alone[95,96]. All these conflicting results suggest that more well-conducted randomised controlled trials are needed to produce strong evidences about it.…”
Section: Intra-operativementioning
confidence: 99%